2019
DOI: 10.1080/10826084.2018.1564330
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Smokeless Tobacco Susceptibility, Initiation, and Progression Over Time Among Adolescents in a Rural Cohort

Abstract: Background: Use of smokeless tobacco (ST, moist snuff and chewing tobacco) is elevated among male rural youth, particularly participants in certain sports, including baseball. Objectives: This study aimed to assess factors associated with adolescent male athletes' STrelated behaviors over time, including: baseline use, initiation, and progression in use intensity in a school-based longitudinal cohort. Methods: Baseline and one-year follow up questionnaires assessed socio-demographic characteristics, environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…[14][15][16] Similar to previous studies, we found alcohol use was associated with new hookah use in youth and young adults, 12 as was marijuana and previous tobacco use. 27 For smokeless tobacco, consistent with other studies of youth, alcohol use was associated with new smokeless tobacco use, 13 although the same was not true of young adults. Few studies have examined initiation of cigars in youth, although our study found correlates of initiation for cigars was similar to those of cigarettes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[14][15][16] Similar to previous studies, we found alcohol use was associated with new hookah use in youth and young adults, 12 as was marijuana and previous tobacco use. 27 For smokeless tobacco, consistent with other studies of youth, alcohol use was associated with new smokeless tobacco use, 13 although the same was not true of young adults. Few studies have examined initiation of cigars in youth, although our study found correlates of initiation for cigars was similar to those of cigarettes.…”
Section: Discussionsupporting
confidence: 81%
“…The exception is Kasza et al, who recently documented correlates of initiation across products through Wave 3 [W3] of the PATH Study, finding that previous tobacco use consistently predicted tobacco product initiation, and some demographic predictors (sex, race/ethnicity and sexual orientation) varied across products. 11 Other studies have found that correlates of non-cigarette products have included alcohol use, 12,13 exposure to others using the products, [14][15][16] mental health, 9 peer use, 7 and receptivity to tobacco advertising. 8 The aim of this study is to expand upon previous PATH Study analyses 5,8,9,11,14,[17][18][19][20] by presenting population estimates of tobacco product initiation and correlates of initiation of each product among youth and young adults between W1 (2013-2014) and Wave 4 (W4, 2016-Jan 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A rural North Carolina study showed that Black and Native American persons were more likely to use “snuff”, whereas Native Americans were more likely to use chewing tobacco compared to their White counterparts [ 102 ]. Another study showed that among a rural cohort of adolescents in California, non-Hispanic White teens were more likely to use smokeless tobacco compared to their rural Hispanic counterparts [ 103 ].…”
Section: Rural and Racial/ethnic Disparities In Cancer Across The mentioning
confidence: 99%
“…Increased exposure to tobacco marketing is consistently associated with cigarette smoking, SLT use, and e-cigarette use among youth [ 4 , 5 , 6 , 7 , 8 ]. Youths’ receptivity to tobacco advertisements (operationalized as their ability to name a favorite brand and owning or being willing to own a tobacco promotional item) is also associated with use of these products [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this theoretical framework exists, our understanding of the associations between cognitive and affective responses to tobacco advertisements and tobacco use outcomes among youth is limited. A large body of research has investigated the associations between advertisement exposures, advertisement receptivity, and tobacco use [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Beyond receptivity, much less is understood about associations between youths’ other cognitive and affective responses toward advertisements and tobacco use.…”
Section: Introductionmentioning
confidence: 99%